Governance and complexity in water management creating cooperation through boundary spanning strategies - Bressers, Hans.; Lulofs, K. R. D.; Edward Elgar Publishing (Cheltenham : Edward Elgar, 2010)
The premise of this book is that careful reconsideration of strategies to achieve water management ambitions, together with more in-depth knowledge on the theories and practices of boundary spanning, could bring solutions for contemporary water problems within reach.
1. Innovations in water management requiring boundary spanning : roots and concepts / Kris Lulofs and Hans Bressers -- 2. Analysis of boundary judgements in complex interaction processes / Hans Bressers and Kris Lulofs -- 3. A boundary perspective on flood management in the Netherlands / Wim van Leussen -- 4. The temporal dimensions of boundary judgements / Aysun Özen Tacer -- 5. Space for water and boundary spanning governance / Hans Bressers, Simone Hanegraaff and Kris Lulofs -- 6. Building a new river and boundary spanning governance / Hans Bressers, Simone Hanegraaff and Kris Lulofs -- 7. The Dutch. land use re-ordering process as a multi-stakeholder management strategy / Katharine Owens -- 8. Linking natural science-based knowledge to governance strategy : a case of regional water depletion analyzed / Mirjam van Tilburg -- 9. Rethinking boundaries in implementation processes / Jaap Evers -- 10. Guidance schemes for the boundary / Spanner Jan van der Molen and Kris Lulofs -- 11. Conclusions / Hans Bressers and Kris Lulofs.
Includes bibliographical references and index.
Keywords: Water-supply -- International cooperation; Water resources development -- International cooperation; Water-supply -- Management; Electronic books